Effect of Forearm Dynamic Taping on Muscle Activity of Extensor Carpi Radialis Brevis During Wrist Isometric and Isotonic Contraction - Tian-zong Huang; Suhn-yeop Kim (Korean Research Society of Physical Therapy, 2021)
Background: Lateral epicondylitis (LE) is the most common chronic musculoskeletal conditions of the upper extremity with pain and wrist extension disability. The tendon which is most affected is the extensor carpi radialis brevis (ECRB). Previous study evaluated the effect of taping technique on patient with LE, but no study investigated the changes of electromyography (EMG) on ECRB when using dynamic taping (DT) technique. Objects: The aim of this study was to investigate the effect of DT technique using dynamic tape on muscle activity of ECRB during wrist isometric extension, isotonic extension and flexion. Methods: Twenty-one healthy subjects volunteered to participate in this study. Subjects were instructed to perform wrist isometric extension, isotonic extension and flexion without and with DT on origin area of ECRB. Wrist isometric extension was performed at 75%, 50% and 25% (%maximal voluntary contraction force), respectively, based on maximum contraction force. Isotonic extension and flexion test used dumbbell. EMG data was collected from ECRB. Results: EMG of ECRB were statistically significant decrease in wrist isotonic extension after DT (p < 0.05). Significant increase in wrist isometric extension during 25% and 50% force task (p < 0.05). Conclusion: This study applied DT technique to suppress the wrist extensor muscles in 21 healthy adults in their twenties. Change in muscle activity was compared in the ECRB muscle during wrist isometric extension, isotonic extension and flexion task. Based on the results of this study, the DT technique applied to the wrist and forearm area can reduce the load on the wrist extensors when the wrist performs various movements during daily life movements or repetitive tasks, and by using these effects, excessive stress is applied to tennis elbow patients.